CORRELATION OF MEAN PLATELET VOLUME AND SOFA SCORE ON SEPSIS PATIENTS IN INTENSIVE CARE UNIT - Irma Yunita Puspayani; Rose Malfiana; Rizal Zainal; Iche Andriyani Liberty (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Delay in diagnosis and treatment of sepsis can result in a rapid deterioration in the direction of failed circulation, damage to various organs until death. The rating system that is often used to assess the extent of organ damage and the likelihood of death is the SOFA score. Mean platelet volume (MPV) is a measurement of average platelet volume (MPV) that has been routinely, but its correlation with SOFA scores in sepsis is not widely understood. The purpose of this study was to determine the correlation of mean platelet volume (MPV) and SOFA scores in septic patients in the ICU. This research is a descriptive observational study using cross sectional design. The sample size obtained from this study was 87 people. The sample in this study were all patients aged ?18 years who were treated in the intensive care unit of RSUP Dr. Mohammad Hoesin Palembang, both heavenly and medical, fulfilled the criteria for diagnosis of sepsis. The results of correlation analysis using the Pearson test showed that statistically SOFA and MPV scores were positively correlated positively with moderate strength (0.5732). This shows that the increase in MPV is directly proportional to the increase in sofa scores in predicting death in sepsis patients.